Polymorphism in the microsatellite located in the promoters of the Tnfa and Tnfb genes of different mouse strains - Iraqi, F.A.; Teale, A.J. (Springer, 1998)
The tumor necrosis factor (TNF) locus comprises the tandemly arranged genes coding for Tnfa (cachectin) and Tnfb (lymphotoxin-alpha) (Semon et al 1987). In mice, the TNF locus is located on chromosome 17 (MMU17) in the major histocompatibility complex (MHC) region. Tnfa and soluble lymphotoxin alpha are cytokines with similar biological activities. Tnfa, a pleiotropic cytokine that is predominatly produced by activated macrophages (Beutler et al 1985) exerts diverse effects on a wide variety of cells including tumor cells lymphocytes fibroblasts and endothelial cells (Beutler and Cerami 1989). Tnfa has also been shown to play an important role in inflammatory immunoregulatory proliferative and antiviral responses and to be important during infection with various protozoan parasites (Beulter and Cerami 1989). Recently we cloned and sequenced the Tnfa genes of three inbred mouse strains. A/J. BALB/C and C57BL/6 (Iraqi and Teale 1997). A polymorphism differentiating the C57BL/6 from the A/J and BALB/C strains was found in the microsatellite (AC)n located in the promoter region. This microsatellite was referred to as a poly (A) repeat by Semon and co-workers (1987). In the latter study a (TC)n microsatellite was reported in the Tnfb promoter. It was suggested that microsatellite repeats in general may be involved in regulation of gene expression (Hamada et al 1982: Lue et al 1989). Moreover it has been observed that increaed repeat lengths of the mi-crosatellite in promoter regions is associated with in-creased gene transcription (Hamada et al 1984). These observations have suggested that the microsatellite may act as enhancer elements or upstream activation sequences (UASs). Here we report length variation in the micro-setellites located in the promoters of the Tnfa and Tnfb genes of 12 mouse strains. Genomic DNA of all 12 strains (C57BL/10J, C57BL/6J, C57B/SgSnj, AKR/A, C3H/Hej, BALB/C, DBA/1J, 129J SWR/J, DBA/2J, A/WySnJ and A/J was obtained from the Jackson Laboratory (Bar Harbor Me).